EFFECTIVENESS OF APPLICATION OF ACQUISITION IN ENERGY SECTOR AND MINING COMPANIES IN INDONESIA - Asegaf, Fatimah Tsaralya; Manalu, Sahala (Universitas Brawijaya, Indonesia, 2018)
The purpose of this study is to determine the difference in the acquirer's financial performance as measured by the current ratio of debt to equity ratio of the operating profit margin net profit margin return on investment return on equity between before and after the acquisition. The type of research used is comparative, the object of study used is energy and mining companies that conduct acquisitions listed on the Indonesia Stock Exchange between 2010-2015. The sampling technique used purposive sampling so that ten companies of energy and mining sector acquired the acquisition activity during the 2010-2015 period whose financial statements are listed in Indonesia Stock Exchange. Test results using Paired Sample t-Test show that four financial ratios do not experience significant differences, namely current ratio, operating profit margin, return on investment and return on equity and two ratios that are different, that is the ratio of debt to equity ratio, net profit margin.